Algunos aspectos sobre la biologia, ecologia, dano economico y control de Chilomina clarkei (Amsel) (Lepidoptera, Pyralidae) barrenador de la yuca - Löhr, Bernhard (International Center for Tropical Agriculture, 1981)
The biology, behavior, ecology, economic damage, and control of the cassava stemborer Chilomina clarkei are described. Its natural enemies found are listed: Agathis sp., Bracon sp., Apanteles sp., Brachymeria sp., and Trichogramma sp. The economic damage in artificial infestations with 2 levels of attack (8-12 and 16-20 larvae/plant) and a treatment of simulated damage breaking stems at 5 mo. were studied. A significant reduction in root yield (62, 45, and 46 percent, resp.) percentage of commercial roots, no. of broken stems, and the no, of cuttings/plant was found. (CIAT)